Determinants of Household Food Security of the Elderly in the Special Region of Yogyakarta - Fera Febriana Sritutur; Bia Satwika Ningrum (JURNAL ECONOMINA, 2026)
The Special Region of Yogyakarta is one of the provinces in Indonesia with a relatively large elderly population. As the number of older adults continues to increase, food security among elderly households has become an important issue that warrants further investigation. This study aims to analyze the determinants of food security among elderly-headed households in the Special Region of Yogyakarta, focusing on demographic, socioeconomic, household, social protection, and regional characteristics. The study utilizes data from the March 2021 National Socioeconomic Survey (SUSENAS). Descriptive statistical analysis and binary logistic regression were employed to examine the determinants of food security. The results indicate that socioeconomic characteristics, particularly poverty, are the most important factors associated with food security among elderly-headed households. Elderly households classified as poor are more likely to experience food insecurity than non-poor elderly households. In addition, the social assistance variable shows a significant negative relationship with food security, indicating that recipients of social assistance are more likely to belong to food-insecure elderly households. This finding also suggests that social assistance programs have relatively succeeded in reaching vulnerable elderly households. Furthermore, age, education, household size, and area of residence are statistically significant determinants of food security among elderly- headed households. The findings imply that improving food security among elderly households requires efforts to reduce poverty, enhance food literacy and nutritional awareness, and strengthen more effective social protection programs targeted at vulnerable elderly population.